Peningkatan Kemampuan Bahasa Inggris Anak-Anak di Kampung Pemulung, Ciputat, Tangerang Selatan - Ika Tri Yunianika; Fauzy Rahman Kosasih; Rahayu Dwi Riyanti; Benny Nugraha (Universitas Mathla'ul Anwar Banten, 2022)
IMPROVING ENGLISH LANGUAGE SKILLS OF CHILDREN IN PEMULUNG VILLAGE, CIPUTAT, TANGERANG SELATAN. This community service program began with an initial discussion to identify the needs of children in Pemulung village. Based on the analysis, it was identified and agreed that the community service would be focused on improving English skills for children through fun learning activities. This program aimed to increase the knowledge of children about the importance of English, provide a fun English learning experience for children, and improve their English language skills. The partners of this program were 36 children aged 5-10 years old and six volunteers from Pos Solidaritas Umat (PSU) LDK Syahid. The programs were conducted by the team in four meetings through presentations from the instructor, small group discussions, and English practices. Furthermore, monitoring and evaluation of these activities were carried out at the end of the programs. The evaluation results show that the partners from PSU LDK Syahid were satisfied with the activities in the program. Besides, most children got enough scores on the program's final test.